Deletion Syndrome 22q11.2: A Systematic Review - Jonathan Cortés-Martín; Nuria López Peñuela; Juan Carlos Sánchez-García; Maria Montiel-Troya; Lourdes Díaz-Rodríguez; Raquel Rodríguez-Blanque (MDPI AG, 2022)
22q11.2 deletion syndrome (DS 22q11.2) is a rare disease of genetic origin, caused by the loss of the q11.2 region of chromosome 22. It affects one in 4000 live newborns, and among the clinical manifestations that can occur in this syndrome are abnormalities in the parathyroid glands (producing calcium deficits), the palate, the heart and the thymus. It is also known as DiGeorge syndrome or velocardiofacial syndrome, among other names, depending on the clinical presentation of each individual. The main objective of the review was to update information on DS 22q11.2 from publications in the scientific literature. The daily activities of these patients are seriously impaired, due to the impact of the clinical manifestations. Interventions can be performed to improve their social, cognitive and emotional skills, thus increasing their ability to perform different daily activities.